Identification and Cross-Characterisation of Artificial Promoters and 5′ Untranslated Regions in Vibrio natriegens - Tietze, Lisa; Mangold, Antonia; Hoff, Maria W.; Lale, Rahmi (Frontiers in Bioengineering and Biotechnology, 2022)
Vibrio natriegens has recently gained attention as a novel fast-growing bacterium in synthetic biology applications. Currently, a limited set of genetic elements optimised for Escherichia coli are used in V. natriegens due to the lack of DNA parts characterised in this novel host. In this study, we report the identification and cross-characterisation of artificial promoters and 5′ untranslated regions (artificial regulatory sequence, ARES) that lead to production of fluorescent proteins with a wide-range of expression levels. We identify and cross-characterise 52 constructs in V. natriegens and E. coli. Furthermore, we report the DNA sequence and motif analysis of the ARESs using various algorithms. With this study, we expand the pool of characterised genetic DNA parts that can be used for different biotechnological applications using V. natriegens as a host microorganism.